Typology of resilience strategies for natural disasters in Yogyakarta city - Guruh Krisnantara; M. Sani Roychansyah (Universitas Gadjah Mada, 2021)
Urban areas in disaster prone require increased capacity in order to reduce the risk level. This study identifies resilience strategies in towards natural disasters in the village unit to obtain detailed data. This study uses field observations to find information about resilience strategies that have been carried out by the government and by the public in general and with snowball sampling techniques in each unit of analysis. Some strategies obtained were then made a typology of strategies found in several villages in the city of Yogyakarta. The results of this study are there are two types of strategies for increasing resilience in Yogyakarta, bottom-up strategy and top-down strategy. Bottom-up strategy is a strategy that was indeed initiated and carried out by the village although in the end it still cannot be separated from the role of main stakeholders, among others, is conducting disaster simulations, training in the use of emergency equipment, disaster socialization, planning, and infrastructure preparation. Top-down strategy is a strategy or policy carried out by the regional government in order to coordinate the level of resilience in the entire region of Yogyakarta, including the addition of the Kampung Tangguh Bencana (KTB), village expansion, organizing volunteers, and infrastructure development.